The combined impact of shallow groundwater and soil salinity on evapotranspiration using remote sensing in an agricultural alluvial setting - Aboelsoud, Hesham; Habib, Ayman; Engel, Bernard A.; Hashem, Ahmed A.; El-Hassan, Waleed Abou; Govind, Ajit; Elnashar, Abdelrazek; Eid, Mona; Kheir, Ahmed M.S. (Elsevier, 2023)
Study region: The Nile Delta, Egypt Study focus: Shallow groundwater (GW) and soil salinity are major issues for irrigated agriculture, particularly in arid and semi-arid regions, but more research is needed to link both issues with evapotranspiration. Satellite-based evapotranspiration from Landsat images (ETLS) has the potential to be an efficient method of estimating evapotranspiration (ET), which can integrate ETLS with groundwater and soil salinity, particularly in data-scarce areas. This study examines shallow GW and soil salinity effects on crop water use in the North Nile Delta during the summer season of 2017 and winter season of 2017/2018. New hydrological insights for the region: The ETLS was moderately affected by groundwater depth (GWD), decreasing from 4.3 to 4.0 mm day− 1 when GWD was reduced from 75 to 120 cm, then increasing to 4.4 mm day− 1 when GWD was increased to 140 cm. The study also highlighted a significant negative correlation between ETgw and GWD; which increased with shallower GW (>75 cm) and then decreased with deeper GW. The shallower the GW, the greater the contribution to crop water requirements, with GW contributing 1.6 and 1.7 mm day− 1 for seed melon and cotton, respectively, while GW contributed 0.9 mm day− 1 for sugar beet and 1.3 mm day− 1 for wheat and clover. The study’s findings highlight the importance of remote sensing and GIS techniques for quickly and cheaply assessing the impact of shallow GW and soil salinity on evapotranspiration over large geographic areas.